PERAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN DAN PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN INDRAMAYU - Suhendar, Suhendar; Kusumah, Riva Rachmi; Salidja, Suhaendi (Yustitia, 2022)
The granting of power to local governments aims to accelerate the realization of welfare for the people in the area through good service, bureaucracy and empowerment. In addition, the regional government is expected to be able to increase regional competitiveness by using all the potential and diversity of the region so that it will also have an impact on the welfare of the regional community. One of the factors that need to be considered by the Regional Government is the economic sector. Local governments need to pay attention to the regional economic sector by paying attention to the potential and diversity of the area so that the area can be economically independent and the local community becomes prosperous. Therefore, local governments can form policies in the form of regional regulations in districts/cities in accordance with their authority in providing empowerment and development to micro, small and medium enterprises.